CITRA PEREMPUAN DALAM TEKS - TEKS BERITA DI HARIAN FAJAR ( Suatu Tinjauan Analisis Wacana Kritis ) - T, Hj. Fatimah (PSW, 2012)
The results showed that in general the news about the woman in the Fajar newspaper, woman have been positioned balanced between positive and negative positions. On the positive position of woman is described as someone who can do many things like men. Woman can excel in sports such as (formula one racer, takrow players, volleyball players, badminton players, karate), education practitioners, real estate businessman, politicians, economic agents (entrepreneurs) and cultural performers. While in the position that woman are portrayed as negative as the weak, the second position only, not confident, take cover behind the beauty, fun dress up, let go, the teaser, materialistic, whores, and, like glamours life.